Decision Support System for Determining Priority Pilgrims at PT Hafiz Wisata Darussalam Based on The C4.5 Algorithm and Profile Matching - Herlina Dianaria; Ermatita; Anggina Primanita (Jurnal Ilmiah Dinamika Rekayasa, 2026)
The increasing competition among Umrah travel service providers requires companies to optimize the use of historical data to support decision-making. PT Hafiz Wisata Darussalam possesses approximately 500 historical records of Umrah pilgrims from the 2022–2025 period; however, these data have not been fully utilized, resulting in a subjective process for determining priority pilgrims. This study aims to develop a Decision Support System (DSS) for determining priority pilgrims by integrating the C4.5 algorithm and the Profile Matching method. The study employed 500 historical records consisting of the following attributes: previous pilgrim status, occupation, social media activity, Umrah package, age, and family group departure. The C4.5 algorithm was applied to classify priority pilgrims by identifying the most influential attributes through a decision tree, while the Profile Matching method was used to rank pilgrims based on their similarity to the company's ideal profile. The system was implemented using PHP and MySQL. The experimental results show that the C4.5 algorithm achieved an accuracy of 82.6%, a precision of 81.5%, a recall of 81.2%, and an F1-score of 81.4%. Out of 500 historical records, the system identified 233 priority pilgrims, who were subsequently ranked using the Profile Matching method to generate objective priority recommendations. The proposed system assists the company in identifying appropriate marketing targets, improving alumni pilgrim loyalty, and supporting more effective and data-driven decision-making.